2011
DOI: 10.18517/ijaseit.1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Copolymer Dehypon® LS 54 and Its Application for Aqueous Two-Phase Systems Paired with the Waxy Maize Starch for Protein Extraction

Abstract: A thermo-separating aqueous two-phase system composed of Dehypon ® LS 54, a polymeric surfactant and the waxy maize starch (amylopectin starch) has been used for partitioning of cutinase as a model protein. Dehypon ® LS 54 were characterized by using 1 H NMR spectroscopy to get information regarding the chemical structure and to confirm the presence of aliphatic moiety group in this copolymer. The phase diagram obtained for these novel polymer-polymers two-phase system shows two-phases with high polymer concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For instance, decellularisation of rat hearts with SDS in pulsatile flow retains most of the GAGs in the ECM (Park et al, 2018). Likewise, optimisation of the decellularisation protocol can significantly enhance the remaining GAG content in a decellularised -Jünger et al, 2016). GAGs are important for the visco-elastic properties of tissues (Lovekamp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, decellularisation of rat hearts with SDS in pulsatile flow retains most of the GAGs in the ECM (Park et al, 2018). Likewise, optimisation of the decellularisation protocol can significantly enhance the remaining GAG content in a decellularised -Jünger et al, 2016). GAGs are important for the visco-elastic properties of tissues (Lovekamp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the skin was immediately treated according to the section "scCO 2 treatment". scCO 2 treatment Based on the protocols described by others (Guler et al, 2017;Huang et al, 2017;Sawada et al, 2008;Wang et al, 2017), scCO 2 was used to eliminate cellular components from the tissues (Fig. 1).…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, maize was selected as a model plant due to its significant economic value as a worldwide cultivated crop for its high starch content [31,32]. Furthermore, studies revealed that the laser is useful to improve the sanitary quality of maize seed [33]; this characteristic allows a seedling to have more strength to emerge from the soil [34].…”
Section: Introductionmentioning
confidence: 99%